Online language learning strategies in Institutes of Higher Learning (IPT) Malaysia post Covid-19 - Nordin, Fitri Nurul 'Ain; Ahmad, Nor Zahidah; Asbulah, Lily Hanefarezan; Ahmad Safian, Nursafira (2023)
The Covid-19 pandemic that spreaded around the world in March 2020 has changed the nation’s education landscape. Standard Operating Procedures that demand presence at respective residences have made online learning one of the best platforms that replace face-to-face learning in educational institutions across the country. Thus, this study aims to propose an effective online language learning strategy to be a reference for educators and students to master language skills using post-Covid19 educational technology. The study was conducted in three phases; literature review analysis, construction of research instruments as well as analyzing the data. The research instruments is questionnaires. A total of 280 respondents consisting of university students in the Arabic field at Malaysian universities answered the questionnaire. The results showed that the respondents got more ideas about how to learn well through online learning than studying in the classroom with a mean rate of 3.39. Among the online learning strategies used by students are always sharing opinions during online learning, responding using chat rooms to engage in discussions and making notes to improve understanding. Respondents are also satisfied with online learning platforms such as google meet, webex and zoom.